Climate change and human impact in central Spain during Roman times: High-resolution multi-proxy analysis of a tufa lake record (Somolinos, 1280m asl) - Currás, a; Zamora, L.; Reed, J. M.; García-Soto, E.; Ferrero, S.; Armengol, X.; Mezquita-Joanes, F.; Marqués, M. a; Riera, S.; Julià, R. (Catena, 2012)
The Roman Period is considered a crucial phase in the evolution of Holocene landscapes, due to the coincidence of major climatic, environmental, economic and cultural changes. However, there is still debate as to the regional expression of these changes, and to the mechanisms involved, particularly in the topographically and climatically complex region of the Mediterranean. In order to improve our understanding of the synergies between societal and environmental change during this period in central Spain, we present a comprehensive case study based on the integration of multi-proxy palaeoenvironmental, archaeological and historical data. High-resolution, interdisciplinary research has been performed on a 3.8 m thick sediment record from the Somolinos tufa lake (1280 m asl), located in a continental Mediterranean area. The analyses include pollen, non-pollen palynomorphs (NPPs), macrocharcoal, ostracods, diatoms, other biotic remains and sedimentology. The Somolinos sequence extends from the 9th century cal BC (Pre-Roman) to the 8th century AD (Early Medieval). The multi-proxy data reveal substantial climate variability during this period. More humid conditions prevailed from 700 to 250 cal BC, while the climate became more arid during the Roman Period (50 cal BC to 70 cal AD). Later on, increased humidity characterized the period from 100 cal AD to 400 cal AD, followed by a progressive arid phase (400 to 715 cal AD) that culminated in total desiccation of the lake. During this time the Romans introduced a new and complex system of resource management in the area, including large-scale farming, grazing, forestry and mining. A strong shift in land use occurred after 80 cal BC, resulting in extensive woodland clearing throughout the range, and in an enhancement of soil erosion and lake productivity. The high-resolution analysis indicates that the peak in Roman impact occurred one century later than the climate changed towards drier conditions. In contrast, social–economical decline and aridiﬁcation were synchronous in Visigothic times (from 5th to 8th centuries AD). The Somolinos record indicates that Roman ‘humid period’ is not a simple phase as some suggest. The observed environmental changes resulted from the interaction of different driving factors.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Central Spain; Land-use change; Marl lake; Palaeoenvironment; Palaeolimnology; Roman Warm Period